السياسة الأوربية للجوار: دراسة في مُكوّن ضبط الآثار السلبية للجوار على الأمن الأوربي - بوعمامة, زهير (revue mofakir, 2018)
السياسة الأوربية للجوار: دراسة في مُكوّن ضبط الآثار السلبية للجوار على الأمن الأوربي